IDENTIFIKASI KONTAMINASI TELUR SOIL TRANSMITTED HELMINTH PADA SELADA (LACTUCA SATIVA) YANG DI PANEN UNTUK KEBUTUHAN KONSUMSI DI KOTA DEPOK JAWA BARAT - Fauzie, Ratu Hunainah (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2026)
Factors that cause contamination from STH eggs include consuming vegetables in raw, unwashed, and not cooked properly. The purpose of this study was to determine the contamination of STH eggs in lettuce (Lactuca sativa) sold in two traditional markets, namely Citayam Market and Pucung Market in Depok City. This type of research is descriptive research with a qualitative approach and purposive sampling design. The research sample consisted of 10 lettuce samples,5 each from Citayam Market and 5 from Pucung Market. The samples were examined in the STKIP Arrahmaniyah laboratory using the sedimentation method. The examination was carried out through the stages of soaking with 0.9% physiological NaCl solution, filtering, centrifuging, and microscopic observation at 10x and 40x magnification. The results showed that all samples (100%) were positive for STH egg contamination. In Citayam Market, 38 eggs were found consisting of 34 Ascaris sp. eggs and 4 Trichuris sp. eggs. Meanwhile, in Pucung Market, 51 eggs were found, consisting of 46 Ascaris sp. eggs, 5 Trichuris sp. eggs, and 1 hookworm egg. The most dominant type of egg found was Ascaris sp. These results indicate that lettuce sold in traditional markets has a high potential risk of intestinal worm infection if consumed without thorough washing.